Effect of Refined Petroleum Product (Kerosene) Flame and Fumes on Serum Enzyme Characteristics of Broiler Chickens - Amakiri, A.O.; Owen, O.J.; Ngodigha, E.M.; Jack, D.O. (International Journal of Poultry Science, 2008)
Enzyme serology of broiler chickens exposed to refined petroleum product (kerosene) flame and fumes at varying distances over a period of 16 hrs daily for 56 days in a poultry house was evaluated. The burning of kerosene was simulated in a designed burner. The measured distances were 4m, 8m and 12m from the flame point. The control birds were located in a separate poultry building without the flame treatment. Proprietary broiler starter and finisher diets were fed ad libitum. Blood samples were taken at the 4th and 8th weeks for enzymological assay from each treatment. The enzymes assayed were Serum Glutamic Oxaloacetic Transaminase (SGOT), Serum Glutamic Pyruvic Transaminase (SGPT) and Alkaline Phosphatase (ALP). No significant (P > 0.05) differences were observed in Serum Glutamic Pyruvic Transaminase (SGPT) and Alkaline Phosphatase (ALP). Results also showed that there were significant differences (P < 0.05) in Serum Glutamic Oxaloacetic Transaminase (SGOT).